RESPON TANAMAN ROSELA BUNGA MERAH (Hibiscus sabdariffa L.) TERHADAP APLIKASI FUNGI MIKORIZA ARBUSKULA DAN PUPUK UREA PADA TANAH JENIS GRUMOSOL (VERTISOLS) - Sinar Suryawati; Slamet Supriyadi; - Mahsun; Masrukhatin Na’imah (Universitas Trunojoyo Madura, 2011)
This research aims to study the effect of combined aplication Arbuscular Mycorrhiza (AM) and Urea to the growth, productivity and quality of roselle plants (Hibiscus sabdariffa L.). The research was conducted at the experimental garden and the Laboratory of Agroecotechnology Department, Faculty of Agriculture, University of Trunojoyo. The study consist of six treatment combinations, repeated 3 times, and based on randomized block design. The observation parameters includes the growth, production and quality of leaf and flower. ANOVA showed that there is no significant effect of combination of AMF and urea on growth parameters, productivity and leaf quality observations, but the real impact on the quality of flowers. Aplication of urea up to 50 kg / ha is still giving the highest effect on growth, plant productivity, vitamine C and protein rosella flowers but decreased the content of vitamin C and protein of leaves. Aplication of AM up to 5 g / plant had the same pattern with the aplication of urea.